Phenotypic changes in transgenic tobacco plants overexpressing vacuole-targeted Thermotoga maritima BglB related to elevated levels of liberated hormones - Nguyen, Quynh Anh; Lee, Dae-seok; Jung, Jakyun; Bae, Hyeun-Jong (Frontiers in Bioengineering and Biotechnology, 2015)
The hyperthermostable β-glucosidase BglB of Thermotoga maritima was modified by adding a short C-terminal tetrapeptide (AFVY, which transports phaseolin to the vacuole, to its C-terminal sequence). The modified β-glucosidase BglB was transformed into tobacco (Nicotiana tabacum L.) plants. We observed a range of significant phenotypic changes in the transgenic plants compared to the wild-type (WT) plants. The transgenic plants had faster stem growth, earlier flowering, enhanced root systems development, an increased biomass biosynthesis rate, and higher salt stress tolerance in young plants compared to WT. In addition, programed cell death was enhanced in mature plants. Furthermore, the C-terminal AFVY tetrapeptide efficiently sorted T. maritima BglB into the vacuole, which was maintained in an active form and could perform its glycoside hydrolysis function on hormone conjugates, leading to elevated hormone [abscisic acid (ABA), indole 3-acetic acid (IAA), and cytokinin] levels that likely contributed to the phenotypic changes in the transgenic plants. The elevation of cytokinin led to upregulation of the transcription factor WUSCHELL, a homeodomain factor that regulates the development, division, and reproduction of stem cells in the shoot apical meristems. Elevation of IAA led to enhanced root development, and the elevation of ABA contributed to enhanced tolerance to salt stress and programed cell death. These results suggest that overexpressing vacuole-targeted T. maritima BglB may have several advantages for molecular farming technology to improve multiple targets, including enhanced production of the β-glucosidase BglB, increased biomass, and shortened developmental stages, that could play pivotal roles in bioenergy and biofuel production.